An Analysis of Job Performance Among Academic Staff of Federal Polytechnic Offa, Kwara State - Raji, Sikirat Abiodun (Mediterranean Journal of Social Sciences, 2012)
This paper conducted a study on Assessment of Job Performance among academic staff of FederalPo1ytechnic Offa, Kwara State. Two research questions and hypotheses each were formulated for this studyinvolving a random sample of two hundred (200) respondents’ from a total population of five hundred andseventy-three (573). Structured questionnaire was the research instrument employed for data collection. Itwas however, analyzed using Pearson product moment co-efficient of correlation (PPMC) statisticalprocedure. The study reveals a number of findings among which were; condition of service are essential toeffective job performance and it also recommended that management boards should review condition ofservice of academic staff favourably with enabling working situations.